Inclusion of Linseed (Linum usitatissimum) Meal on the Performance of Vanaraja Birds (Indian Journal of Animal Production and Management, 2024)
The present study was carried out with the  objective of studying the reproductive performance,  blood constituents and economics of rearing  Vanaraja birds as influenced by the dietary  inclusion of linseed meal. The study was conducted  at the poultry unit of the department. A total of 120  female Vanaraja chicks were reared for a period of  nine months and were randomly divided into four  treatment groups (T1, T2, T3, and T4) of 30 birds,  each having five replications per treatment following  a randomized block design. They were subjected to  four dietary levels of linseed meal, containing 0%,  4%, 8%, and 12%, respectively. The birds were  reared under a deep litter system up to 8 weeks of  age and thereafter in cages following standard  management practices. Initial body weight was  recorded at 1 day old, and thereafter it was  recorded fortnightly. Feed intake and egg  production were recorded daily. The control group  had higher egg production, clutch size, and egg  weight. Higher yolk weight, albumen weight, and  yolk cholesterol were recorded in T3, while group T4  had the maximum HU. The lowest cholesterol and  triglycerides were recorded in T4, while the highest  HDL and lowest LDL were observed in the control  group. The cost of production was highest in T4 and  lowest in T2, while higher net profit per bird and net  profit per gain were recorded in T3 as compared to  the control group.
Keywords: Vanaraja birds; egg quality; blood biochemical parameters; egg production